Democracy's debt : the historical tensions between political and economic liberty - Bruner, Michael Lane, 1958- (Amherst, N.Y. : Humanity Books, 2009)
"It is an undeniable fact that economic circumstances can directly impact political affairs, that wealth is easily translated into political influence, and that political movements and constitutional arrangements can directly influence economic environments. There is no consensus, however, on how to best manage the tensions between the production and maintenance of wealth and the just and responsible exercise of political power." "In an in-depth analysis of these historic tensions, Professor of Communication M. Lane Bruner surveys the history of argumentation related to wealth and statecraft, and, more important, the actual economic and political practices in republican polities of the past to compare arguments to policies. The overriding goal of the study is to analyze which forms of governance have provided the most useful guides for the reform of contemporary institutions in charge of global governance." "Bruner begins by discussing the interrelationships among forces of the state, the market, and argumentation, and then summarizes the historical "triumph" of economic liberty over political liberty. Next he provides a brief history of the idea of free trade and associated economic arguments from ancient Greece to the eighteenth century. Subsequent chapters focus on the Italian Renaissance republics as the first historical example of the problematic relationship between republicanism and economic practice; on the tensions between economics and politics as reflected in England's "financial revolution" in the seventeenth and eighteenth centuries; on the American revolution and the economic struggles surrounding the development of the US Constitution; on the rise of economic globalization and attempts to create a "global constitution" for international finance; and, finally, on the dominant rhetorical strategies in the current globalization debate and the future trajectory of global constitutionalism."--BOOK JACKET.
Ch. 1. Economics, Politics, and Rhetoric -- Ch. 2. A Brief History of Economic Liberty -- Ch. 3. Virtue, Finance, and Government -- Ch. 4. Debt and Constitutionalism in Revolutionary England -- Ch. 5. Economic and Political Liberty in Revolutionary America -- Ch. 6. Economic Globalization and the Critical Public -- Ch. 7. Global Constitutionalism.
Includes bibliographical references (p. 357-375) and index.
Keywords: Democracy; Political science; Economics